Competition Policy for High Technology Industries - Stephen Martin (Tinbergen Institute, 2000)
I model optimal product-market competition policy when industriesdiffer inthe potential for quality-improving technological advance. In a two-periodmodel, a competition authority with limited resources administers adeterrence-based competition policy toward two industries. In one oftheindustries, an incumbent firm chooses the level of resources toinvest in aquality-improving R&D project. In the other industry, product qualityisconstant. The competition authority cannot commit in advance to thetoughness of competition policy in the post-discovery world. Optimalpolicy requires the competition authority to administer a toughercompetition policy before innovation, all else equal, the greater thepotential quality improvement; patent protection may increase R&Dintensity, but worsens market performance.
Keywords: 330; Wettbewerbspolitik; Hochtechnologie; Theorie